A contribution to the sawfly fauna of northern Greece (Hymenoptera, Symphyta). - Blank, Stephan M. (Contributions to Entomology = Beiträge zur Entomologie, 1993)
This contribution to the Greek sawfly fauna reports on 41 species of Symphyta from Macedonia and Epirus. Nineteen of them are recorded from Greece probably for the first time: Aprosthema austriaca (Konow, 1892), Strongylogaster xanthocera Stephens, 1835, Scolioneura spec., Athalia cornubiae Benson, 1931, A. paradoxa Konow, 1886, Monostegia abdominalis (Fabricius, 1798), Allantus cingulatus (Scopoli, 1763), Tenthredo brevicornis (Konow, 1886), T. livida Linnaeus, 1758, T. maculata semseyi Mocsáry, 1883, T. marginella marginella Fabricius, 1793, T. notha notha Klug, 1817, T. obsoleta Klug, 1817, T. amoena Gravenhorst, 1807, Rhogogaster viridis (Linnaeus, 1758), Macrophya rufipes orientalis Mocsáry, 1891, M. rufopicta Enslin, 1910, Aglaostigma aucupariae aucupariae (Klug, 1817), Pontania kriechbaumeri (Konow, 1901). The Lectotype of Empria abdominalis var. rufinotis Enslin, 1914 (= Monostegia abdominalis Fabricius, 1793) is fixed.Nomenclatural Actsrufinotis Enslin, 1914 (Empria abdominalis var.), Lectotype now a synonym of Monostegia abdominalis (Fabricius, 1798)